MATHEMATICS LEARNING BASED ON EXPERIMENTAL LEARNING DESIGN IN FRACTION CONCEPT FOR PGMI STUDENTS - Zikra Hayati (PIONIR: JURNAL PENDIDIKAN, 2021)
In reality, Fraction is one of a difficult subject in mathematics, to learn as well as to teach its. Most of students have a complex to comprehend the fraction concept and operation. As same as a teacher have a difficult way when they are teach it, they encourage students just to memorize the formula, give some rules to solve and applied. A lot of teacher did not use a manipulative media for enriching their learning. This was a negative impact for teaching and learning, they are not using manipulative media to build fraction concept. Bad affect, students are not interested to learn about the fraction. In this study, researchers applied the Qualitative approach, the aims of this are (1) Analyze and describing systematically about the beginning comprehend of PGMI students about fraction concept, (2) the realization of applying experimentallearning  and  usage manipulative media in  fractios. Thus, the outcomes of this research would be the result about the beginning comprehensive student’s PGMI about the fraction concept and manipulative media is implemented to teach the fraction. Based on the first data, it can be concluded that PGMI students have a difficult to explain about (1) determine the fraction part of an area (2) teach and explain the concept of fraction for elementary students (3) solving a fractional operation (4) defining a fraction worth (5) usage manipulative media for the concept of fraction.